Український напрямок зовнішньої політики БНР [Білоруської Народної Республіки] (1918 – 1921 рр.) - Дедурін, Г. Г.; Dedurin, G. G.; ORCID: http://orcid.org/0000-0002-5277-023X (Наукові записки Тернопільського національного педагогічного університету ім. В. Гнатюка. Серія: Історія. - 2017. - Вип. 2, ч. 2. - С. 107-112, 2017)
Завершення Першої світової війни, революції у Росії та країнах Європи відчутно активізували процеси націотворення серед молодих народів Європи, зокрема білорусів і українців. Великі держави не надто прихильно ставилися до їх державницьких устремлінь, що робило вкрай важливим налагодженнями взаємодії між цими народами. Українці дещо раніше спромоглися створити власну республіку та оголосити її незалежність. Крім того, УНР були визнана низкою країн, зокрема Німеччиною. Це робило позиції українців у взаємовідносинах з білорусами більш виграшними. Починаючи з квітня 1918 р., БНР кілька разів надсилала свої делегації до Києва, головною метою яких було офіційне визнання Білоруської республіки з боку України та встановлення між ними справедливих кордонів. Проте, слабка підготовленість до переговорів білоруських делегатів, часта зміна політичних режимів в Україні та загальна несприятлива для обох молодих республік міжнародна ситуація, не дозволила досягти значних результатів, які б вплинули на подальшу їх долю.

At the final stage of the I World War, the national movements of a number of peoples of Central and Eastern Europe, which sought to gain their own statehood, became more active. Under these circumstances, the leadership of the BNR needed to establish constructive relations with its closest neighbors: the Poles, Lithuanians, Ukrainians. A few days after the proclamation of the independence of the BNR on March 25, 1918, a diplomatic mission was sent to Kiev from the Belarusian government headed by A. Tsvikevich, who met almost all the leaders of the Central Rada, including M. Hrushevsky, in early April. This mission was in fact the first diplomatic experience of the young republic. Ukrainian politicians, on the whole, reacted positively to the content of the Third Charter, noting their interest in creating a friendly neutral state on their borders, but they did not hurry to recognize the BNR, referring to the terms of the Treaty of Brest-Litovsk. The issue of disputed territories in the Belarusian-Ukrainian borderland remained unresolved. The plans of the Ukrainian-Belarusian federation were not to be realized. The Ukrainian side did not differ in consistency in its foreign policy strategy and in the conditions of a very shaky domestic political situation, was interested in a dialogue with those forces that could give it real help. The Ukrainian politicians did not see the Belarusians among them. After of the Treaty of Riga in March 18, 1921 between Poland and Soviet Russia put both sides at a very disadvantageous position in the international arena, forcing us to regretfully recall the opportunities missed earlier for more effective cooperation.

Завершение Первой мировой войны, революции в России и странах Европы ощутимо активизировали процессы формирования наций среди молодых народов Европы, в том числе белорусов и украинцев. Великие державы не слишком благосклонно относились к их государственным устремлениям, что делало крайне важным налаживание взаимодействия между этими народами. Украинцы несколько раньше смогли создать собственную республику и объявить ее независимость. Кроме того, УНР были признана рядом стран, в частности Германией. Это делало позиции Украины во взаимоотношениях с белорусами более выигрышными. Начиная с апреля 1918 г., БНР несколько раз посылала свои делегации в Киев, главной целью которых было официальное признание Белорусской республики со стороны Украины и установления между ними справедливых границ. Однако, слабая подготовленность к переговорам белорусских делегатов, частая смена политических режимов в Украине и общая неблагоприятная для обоих молодых республик международная ситуация не позволили достичь значительных результатов, которые бы повлияли на дальнейшую их судьбу.
Ukrainian direction of foreign policy BNR (1918–1921)
Дедурін, Г. Український напрямок зовнішньої політики БНР (1918 – 1921 рр.) / Геннадій Дедурін // Наукові записки Тернопільського національного педагогічного університету ім. В. Гнатюка. Серія: Історія. - 2017. - Вип. 2, ч. 2. - С. 107-112.
Keywords: Історія. Культура. History. Culture. История. Культура; Історія. History. История; Наукові публікації. Scientific publications. Научные публикации; політика; Білоруська Народна Республіка; Українська Народна Республіка; дипломатія; кордони; федерація; Belarusian People’s Republic; Ukrainian People’s Republic; diplomacy; borders; federation; Белорусская Народная Республика; Украинская Народная Республика; дипломатия; границы; федерация